PREVALENCE AND SOCIODEMOGRAPHIC FACTORS ASSOCIATED WITH SEDENTARY BEHAVIOR IN ADOLESCENTS FROM RIO CLARO-SP, BRAZIL - Christofoletti, Ana Elisa Messetti [UNESP] (2020)
The objective of this study was to analyze the prevalence of and sociodemographic factors associated with sedentary behavior (SB) situations among adolescents from Rio Claro, São Paulo, Brazil, namely: (1) obligations; 2) computer/tablet and video game; 3) smartphone; 4) television; 5) total SB. It included 482 teenagers (14.4 ± 2.1 years old) from 3 public and 2 private schools. They were assessed through an identification, clinical history and socioeconomic level questionnaire; Sedentary Behavior Questionnaire, with additional questions related to SB and use of smartphones and video games; Habitual Physical Activity Questionnaire for Adolescents; and weight and height measurement for Body Mass Index (BMI) calculation (kg/m²). Descriptive analysis was performed, Student’s t test was run to compare SB situations and level of physical activity between boys and girls, and logistic regression was carried out to verify the association of the situations with total SB (p <0.05). Results revealed that 47.5% of the adolescents spend more than 14 hours/day on SB (mean of 13.7 ± 3.4 hours/day). The situations associated with total SB were: smartphone (OR=6.23; p<0.001); computer/tablet and video game (OR=2.5; p=0.012); obligations (OR=2.43; p=0.009) and TV (OR=2.35; p=0.009). High SB prevalence was found, but there was no sociodemographic factor associated with this behavior. Additionally, smartphone use presented a greater association with high amount of time for total SB.